Living with Dementia in Aotearoa (LiDiA): A feasibility study for a dementia prevalence study in Māori and non-Māori Living in New Zealand - Martinez-Ruiz, Adrian; Yates, Susan; Cheung, Gary; Cullum, Sarah; Dudley, Makarena; Krishnamurthi, Rita; Fa'alau, Fuafiva; Kerse, Ngaire; Roberts, Mary; Taufa, Seini; Rivera Rodriguez, Claudia (SAGE Publications, 2023)
INTRODUCTION: Recent estimations have projected a threefold increase in dementia prevalence in Aotearoa New Zealand (NZ) by 2050, particularly in Maori and Pacific peoples. However, to date, there are no national data on dementia prevalence, and overseas data are used to estimate the NZ dementia statistics. The aim of this feasibility study was to prepare the groundwork for the first full-scale NZ dementia prevalence study that is representative of Māori, European, Pacific and Asian peoples living in NZ. METHODS: The main feasibility issues were: (i) Sampling to ensure adequate community representation from the included ethnic groups, (ii) Preparing a workforce to conduct the fieldwork and developing quality control, (iii) Raising awareness of the study in the communities (iv) Maximizing recruitment by door-knocking, (v) Retaining those we have recruited to the study and (vi) Acceptability of study recruitment and assessment using adapted versions of the 10/66 dementia protocol in different ethnic groups living in South Auckland. RESULTS: We found that a probability sampling strategy using NZ Census data was reasonably accurate and all ethnic groups were sampled effectively. We demonstrated that we were able to train up a multi-ethnic workforce consisting of lay interviewers who were able to administer the 10/66 dementia protocol in community settings. The response rate (224/297, 75.5%) at the door-knocking stage was good but attrition at subsequent stages was high and only 75/297 (25.2%) received the full interview. CONCLUSIONS: Our study showed that it would be feasible to conduct a population-based dementia prevalence study using the 10/66 dementia protocol in Māori, European and Asian communities living in NZ, utilizing a qualified, skilled research team representative of the families participating in the study. The study has demonstrated that for recruitment and interviewing in Pacific communities a different but culturally appropriate approach is required.
Keywords: dementia; dementia prevalence; feasibility study; multi-ethnic dementia prevalence; population based study; dementia; dementia prevalence; feasibility study; multi-ethnic dementia prevalence; population based study; 4203 Health Services and Systems; 42 Health Sciences; Acquired Cognitive Impairment; Brain Disorders; Dementia; 1103 Clinical Sciences; 1110 Nursing; 1702 Cognitive Sciences; Geriatrics; 4203 Health services and systems; 4205 Nursing